2003
DOI: 10.1007/s00104-002-0593-3
|View full text |Cite
|
Sign up to set email alerts
|

Zur Behandlung des eingewachsenen Zehennagels

Abstract: In Germany,"Emmert plasty" is one of the terms most frequently used in daily surgical practice. It describes the wedge excision of nail fold, nail edge, and corresponding matrix for advanced stages of ingrown toenail in most standard textbooks of surgery but without direct reference to Emmert. The method, however,was apparently first described by the French military surgeon Baudens in 1850 and was strongly opposed by Emmert himself who propagated a pure soft tissue resection. This text gives a short historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Van der Ham et al 10 found that phenol treatment gave better results than wedge resection. Other methods, such as removal of the complete nail bed and matrix11 or partial nail extraction12, were associated with high recurrence rates of 64–83 per cent8. Gerritsma‐Bleeker and colleagues13 found partial excision of the matrix to be preferable to use of phenol, with recurrence rates of between 10 and 30 per cent, but at the expense of prolonged healing time and/or problems with scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Van der Ham et al 10 found that phenol treatment gave better results than wedge resection. Other methods, such as removal of the complete nail bed and matrix11 or partial nail extraction12, were associated with high recurrence rates of 64–83 per cent8. Gerritsma‐Bleeker and colleagues13 found partial excision of the matrix to be preferable to use of phenol, with recurrence rates of between 10 and 30 per cent, but at the expense of prolonged healing time and/or problems with scarring.…”
Section: Discussionmentioning
confidence: 99%
“…It was also Emmert who had first described the three stages of ingrown toenails [27]. In the late 1800s, there were more similarly radical surgical operations such as those of Hildebrandt 1884 [32]. Anger's method was to cut a section of the toe from its extremity back to beyond the matrix with cuts extending to the bone [33].…”
Section: Treatment Of Ingrown Toenailsmentioning
confidence: 99%